Can international economic agreements combat COVID‐19? - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2020)
The COVID-19 pandemic has significantly disrupted the international economic order. According to the World Trade Organization (WTO), the unprecedented health crisis may sink global trade by 32% in 2020.236 As an island state highly dependent on trade, Singapore is expected to encounter a 5.8% contraction in gross domestic product, marking its “worst recession since independence.”237 The number of confirmed COVID-19 cases in Singapore surpassed the 45,000 mark on July 7, 2020.238 Most cases have occurred in foreign worker dormitories, whereas the spread of the disease in the rest of the community has been limited. To gradually resume economic activities and ease border controls, the Singapore government embarked on a three-phased approach when “circuit breaker” measures that imposed lockdown ended on June 1, 2020.239 Much discussion focuses on Singapore’s domestic policy such as stimulus packages and fiscal measures that provide relief to companies and citizens. 240 Nevertheless, Singapore’s lessreported international law strategy toward the crisis yields salient global implications. Selected Asian states that have reasonably managed the coronavirus outbreak, including Korea, Taiwan and Vietnam, have been able to do so without international assistance. Notably different from the self-reliance approach, Singapore has resorted to a two-pronged legal strategy that is built upon international economic agreements at bilateral and regional levels.